Folic acid supplementation and methylenetetrahydrofolate reductase (MTHFR) gene variations in relation to in vitro fertilization pregnancy outcome. (31st October 2014) - Murto, Tiina; Kallak, Theodora K.; Hoas, Annica; Altmäe, Signe; Salumets, Andres; Nilsson, Torbjörn K.; Skoog Svanberg, Agneta; Wånggren, Kjell; Yngve, Agneta; Stavreus‐Evers, Anneli
Abstract Objective To study folic acid intake, folate status and pregnancy outcome after infertility treatment in women with different infertility diagnoses in relation to methylenetetrahydrofolate reductase (MTHFR) 677C>T, 1298A>C and 1793G>A polymorphisms. Also the use of folic acid supplements, folate status and the frequency of different gene variations were studied in women undergoing infertility treatment and fertile women. Design Observational study. Setting University hospital. Population Women undergoing infertility treatment and healthy, fertile, non‐pregnant women. Methods A questionnaire was used to assess general background data and use of dietary supplements. Blood samples were taken to determine plasma folate and homocysteine levels, and for genomic DNA extraction. A comparison of four studies was performed to assess pregnancy outcome in relation to MTHFR 677 TT vs. CC, and 1298 CC vs. AA polymorphisms. Main outcome measures Folic acid supplement intake, and plasma folate, homocysteine and genomic assays. Results Women in the infertility group used significantly more folic acid supplements and had better folate status than fertile women, but pregnancy outcome after fertility treatment was not dependent on folic acid intake, folate status or MTHFR gene variations. Conclusion High folic acid intakes and MTHFR gene variations seem not to be associated with helping women to achieve pregnancy during or after fertility treatment.